The Khuff Formation (Middle East) and time-equivalents in Turkey and South China: biostratigraphy from Capitanian to Changhsingian times (Permian), new foraminiferal taxa, and palaeogeographical implications - Gaillot, Jérémie; Vachard, Daniel (Coloquios de Paleontología, 2008)
A detailed biostratigraphic and microfacies study of the late Middle Permian to Early Triassic Khuff Formation was undertaken in three reference regions in the Zagros area (Iran), United Arabian Emirates (UAE) and Saudi Arabia. Comparisons done with traditional Lopingian reference sections, as such as Hazro (eastern Taurus, Turkey), and Laren and Tsonteng sections (Guangxi, southern China), allow sub-dividision of the Permian part of the Khuff deposits into six main biozones: (1) the late Midian is characterized by Shanita amosi associated with Dunbarula nana; (2) the early Wuchiapingian is characterized by the FAD of Paraglobivalvulina mira and Pseudotristix solida during a first flooding event, strongly restructuring the Middle Permian habitats; (3) the “middle” Wuchiapingian is defined locally with the appearance of the genus Paradagmarita with numerous regional markers and corresponds to maximal connection with an open marine system; (4) the late Wuchiapingian is characterized by an assemblage dominated by the biseriamminid Charliella altineri sp. nov. and the ozawainellid Neomillerella mirabilis gen. nov. sp. nov.; (5) the early Changhsingian corresponds to a “Biseriamminid bloom” event with Paradagmacrusta callosa gen. nov. sp. nov. as the main marker; and (6) the late Changhsingian is dominated by large miliolids such as Crassiglomella and Glomomidiellopsis uenoi. During the Late Permian, different foraminiferal morphogroups colonized and flourished in the various habitats of the inner carbonate shelf of the Arabian Platform, depending mainly on salinity, energy, depth, and presence of shallow meadows of gymnocodiaceans. Apalaeoecological analysis will be presented in a second part of this work, together with the study of algae. The Late Permian foraminifers of the Khuff platform are typical of very shallow to restricted environments, and cannot cross through deep basins because of its shallow stenobath character. Hence, their geographical distribution can be used to reconstruct the continuity of the inner carbonate ramps. Numerous foraminifer genera were discovered in the different regions. Some biseriamminoid taxa are especially useful to identify the degree of connection and thus the approximative distance between carbonate platforms and/or tectonostratigraphic terranes. Hence, relationships are confirmed between the Taurus and Zagros but, surprinsingly, they are demonstrated between Zagros, southern China and some Japanese terranes. The best palaeobiogeographical markers are Paradagmarita, Floritheca, Partisania and Paradagmaritopsis. The new taxa described here are: (a) 2 subfamilies, Paradagmarininae and Paraglobivalvulininae; (b) 17 genera, Floritheca, Neomillerella, Labioglobivalvulina, Retroseptellina, Labiodagmarita, Paradagmaritella, Paradagmacrusta, Paremiratella, Septigordius, Brunsispirella, Crassispirella, Crassiglomella, Uralogordius, Neodiscopsis, Glomomidiellopsis, Nestellorella, and Aulacophloia; (c) 30 species: Floritheca variata, Neomillerella mirabilis, Globivalvulina parascaphoidea, G. neglecta, Charliella altineri, Labioglobivalvulina baudi, L. fortis, Paremiratella robusta, Labiodagmarita vasleti, Louisettita extraordinaria, Paradagmarita simplex, P. zaninettiae, P. planispiralis, Paradagmaritella brevispira, Paradagmaritella surmehensis, Paradagmacrusta callosa, Paremiratella robusta, Palaeonubecularia iranica, Hoyenella laxa, Crassispirella hughesi, Glomomidiellopsis uenoi, G. tieni, G. lysitiformis, Neodiscopsis canutii, Rectostipulina syzranaeformis, Langella massei, Partisania sigmoidalis, Cryptomorphina hazroensis, Pachyphloia enormis, and Aulacophloia martiniae; and (d) 9 emended genera: Septoglobivalvulina, Louisettita, Hoyenella , Neodiscus, Tauridia, Polarisella, Pachyphloides/Cryptoseptida and Ichthyofrondina.